Review on Fishery in Kerala Perspective - Rajlaxmi Mohanty (MPRA Paper No. 44285, 2013)
This paper investigates Kerala fishery sector and its impact on ecosystem, and socioeconomic impact of ban on fisheries on the fishing labour and their dependence on fishing as livelihood. The paper analyses the viability of various mechanized fishing units in the State of Kerala using different economic and financial indicators. The study aims to provide a background to fisheries in Kerala with focus on seafood export from the State using commodity, quantity, value and country wise data. The study also aims to map the flow of key export species from landing site to the port of dispatch in order to list the main factors that determines the seafood export chains in the state. The report ends with brief note on the degree of dependence of the poor within the fishing community on seafood industry and suggestions on improving the livelihood security of fish workers with resource conservation.